Licensing of Right-of-Way Pesticide Applicators in Florida - Frederick M. Fishel (EDIS)
PI-148, a 2-page fact sheet by Frederick M. Fishel, explains the licensing and regulation of persons who apply restricted use pesticide applications to rights-of-way in Florida. Published by the UF Pesticide Information Office, February 2007.